(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, on the example of the novel of the writer Nazar Eshonkul "Gorogly Yahud Hayot Suvi", the comparative-typological aspect examines the renewal and changes taking place in modern Uzbek "modern" novels, in particular, the experience of creating an anti-hero. Because the artistic reality in this work performs no less a poetic task than real events. In an effort to understand a person and society, the author, using the example of the suffering of a literary hero N, sharply rejects the social environment in which a person is not honored and his dignity is ignored. The writer, using the example of N.’s attempts to overcome life’s trials, sarcastically laughs at the forgotten and imperfect laws of society. It shows the vital essence of the development of society and human thinking.